Comparison of game movement positional profiles between professional club and senior international Rugby Union players - Beard, A.; Chambers, R.; Millet, G. P.; Brocherie, F. (International Journal of Sports Medicine, 2019)
The purpose of this study was to compare the game movement demands between professional club and senior international rugby union players. Data were obtained from 188 players from 4 professional club teams (Rabo Direct Pro12) and the affiliated international team during the 2014-15 season. Players were tracked by global positioning system (GPS) sampled at 10?Hz and were categorized into 6 different positional groups (front row forwards, FRF; second row forwards, SRF; back row forwards, BRF; half backs, HB; centres, C; outside backs, OB) and separated into playing standard (club vs. international level). Data on distance, distance per minute, high speed running, maximum velocity, sprint distance and efforts as well as repeated high-intensity locomotion efforts (RHILE) were collected. Significant effects (P<0 .05) between club and international were found for RHILE in all 6 positional groupings with a higher number of RHILE in international vs. club games. Significantly (P<0.05) greater total distance and meterage were also shown in international compared to club for OB position. The RHILE differences between club and international games whatever the positions appear of practical relevance for coaches and performance staff to concentrate on training protocols to enhance this quality as well as evaluation methods.